Healing and reconciliation. Issue 3 (20th July 2020) - Thomas, James R.
Abstract: The Christian Church is called to the ministry of reconciliation. Despite the pain and struggle of fractured communities today, there are also stories of hope lived and told by persons who are the recipients of the ministry of local congregations and church‐sponsored social service agencies. Reconciliation leads to hope, and hope leads to reconciliation.